Is apomixis occurring in walnut (Juglans regia L.)? New data from progeny molecular tests and cytological investigations shed light on its reproductive system - Solhjoo, Sahar; Fatahi, Reza; Zamani, Zabihollah; Chehregani Rad, Abdolkarim; Palumbo, Fabio; Barcaccia, Gianni (Frontiers in Plant Science, 2023)
Introduction Persian walnut (Juglans regia) is an economically important nut fruit species cultivated worldwide for its nutritious kernel and timber quality wood. Walnut trees are mostly hetero-dichogamous and, depending on the genotype, some cultivars are protogynous, while others are protandrous. Although selfing is possible when male and female blooms overlap, the dichogamy of the species promotes outcrossing. In addition to sexual reproduction, some reports indicate that elements of apomixis may occur in commercial orchards of walnut varieties and in the last two decades, nut production by apomixis has been reported in walnut. However, there are no reliable studies on the occurrence of apomictic reproduction based on cytoembryological observations and/or molecular marker-progeny tests. This study addresses the combined use of molecular and cytological analyses to gain new insights into the population genetics and reproduction systems of J. regia. Methods We systematically analyzed the reproductive origin of individual progeny plants from 8 different cultivated walnut genotypes using microsatellite genotyping and carried out cytohistological investigations of 5 cultivated walnut genotypes arising seed sets from isolated flowers, to shed light on the mode of reproduction. Results and discussion These cytometric and genotyping analyses did not support any asexual mode of reproduction or asexual propagation by seed and all individuals studied were identified as zygotic plants produced by crossing. Likewise, the cytological findings did not confirm completely the first component of apomixis, namely apomeiosis. On the other hand, according to histological evidence, adventitious embryony seems to take place at low frequency. Overall, our findings suggest that the occurrence of gametophytic apomixis is unlikely in J. regia, but sporophytic apomixis cannot be completely ruled out.